Multidisciplinary neurosurgical rounds incorporating antimicrobial stewardship. Are they of benefit? - M. Creedon; H. Humphreys; R. Connolly; L. Gaughan; M. Skally; J. Caird; J. Duddy; P.J. O'Halloran; T. Mandiwanza; K. Burns; B. Dinesh; E. Smyth; et al. (Brain and Spine, 2022)
Background: In an era of increasing antimicrobial resistance, appropriate antimicrobials are essential to optimise patient outcomes. In 2017, antimicrobial use prevalence (AMU) on the two neurosurgical wards in our tertiary teaching hospital varied from 23% on ward A to 33% on ward B with 67% and 100% ‘appropriate’ prescriptions, respectively. In July 2018, a weekly antimicrobial stewardship multidisciplinary round led by a senior neurosurgery registrar commenced, attended by the antimicrobial stewardship team (AST). Research question: This report evaluates whether a multi-disciplinary approach on neurosurgical prescribing was beneficial, specifically in reducing AMU. Materials and methods: The following data was collected on AST rounds for 30 weeks in total from August 2018 to July 2019: number of patients on antimicrobials, appropriateness and stewardship actions. A questionnaire was distributed to neurosurgical doctors on two occasions to canvass opinions and attitudes on antimicrobial prescribing. Results: 1716 prescriptions were reviewed (mean 57.2 per week). Of these 321 (18.7%) included antimicrobial prescriptions; 200 on ward A (19.8%), and 121 on ward B (17%), representing a decrease in AMU from 2017. The majority of antimicrobial prescriptions, 271 (84.4%) were deemed appropriate. Stewardship actions were taken in 215 (67%) prescriptions.Fifteen questionnaires were completed by neurosurgical doctors. The majority, 87%, stated the AST round was helpful overall. 93% indicated that informal training on the AST round was a source of education in antibiotic prescribing. Discussion and conclusion: The weekly AST round provided a timely opportunity for multidisciplinary discussion, implementation of antimicrobial stewardship actions and opportunistic antimicrobial stewardship education.